2017
DOI: 10.3892/etm.2017.4240
|View full text |Cite
|
Sign up to set email alerts
|

Berberis vulgaris extract/β-cyclodextrin complex increases protection of hepatic cells via suppression of apoptosis and lipogenesis pathways

Abstract: Berberis vulgaris (Bv) is well known worldwide for its healing properties. However, limited information is available concerning its mechanism of action and the increased hepatoprotective activity of formulated extracts. This study evaluated the protective effect of Bv bark extract against CCl4-induced cytotoxicity in Huh7 cells, as well whether β-cyclodextrin complexation of the extract resulted in increased hepatoprotective effects. Huh7 cells were incubated for 48 h with 5, 7.5 and 10 µg/ml of unformulated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…32 CCl 4 -induced apoptotic cell death is said to be mediated through the activation of caspase-3/7. 33 In our study, crocin administration ameliorated the CCl 4 -induced liver cells apoptosis by inhibiting the caspase-3/7-dependent apoptotic signalling pathway. Similarly, Sun et al have suggested the role of crocin in reducing cisplatin-induced liver injury via inhibiting p38 mitogen-activated protein kinase (MAPK) and caspase-3 activity.…”
Section: Discussionsupporting
confidence: 50%
“…32 CCl 4 -induced apoptotic cell death is said to be mediated through the activation of caspase-3/7. 33 In our study, crocin administration ameliorated the CCl 4 -induced liver cells apoptosis by inhibiting the caspase-3/7-dependent apoptotic signalling pathway. Similarly, Sun et al have suggested the role of crocin in reducing cisplatin-induced liver injury via inhibiting p38 mitogen-activated protein kinase (MAPK) and caspase-3 activity.…”
Section: Discussionsupporting
confidence: 50%
“…The enzyme activity was evaluated spectrophotometrically using Multiskan™ SkyHigh (Thermo Fisher Scientific), following the method of McQueen (1972) [ 22 ]. The reaction velocity was determined by a decrease in absorbance at 340 nm resulting from the oxidation of NADH (indicative of LDH activity) that was expressed in IU/L [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a study examining the antioxidant properties of B. vulgaris and its cytotoxic effect on human breast cancer cells, it was shown that B. vulgaris has strong antioxidant properties and cytotoxic effects that can induce apoptosis [ 40 ]. In another study examining the apoptotic pathways of B. vulgaris extract in hepatic cells, antiproliferative and proapoptotic effects were evident upon suppressing caspase-3 activation and lipid accumulation [ 48 ]. In another study, B. vulgaris exhibited potent anticancer activities with the induction of apoptosis in esophageal carcinoma cells [ 49 ].…”
Section: Discussionmentioning
confidence: 99%